(untitled) (Philological Studies, 2022)
The article illustrates the importance of gender-marked information as crucial pragmatic information in a lexicographical description of gender-marked idioms. Furthermore, it analyzes the existing practice of lexicographical description of Russian gender-marked idioms and suggests the possibilities of a more consistent way of implementing of this type of pragmatic information in a dictionary definition of idioms. For this purpose, the authors have conducted corpus-based research on the use of chosen idioms and an analysis of the correlation between the lexicographical description of gender-marked idioms and their appropriate use in speakers of Russian as a foreign language. The results indisputably prove a need to incorporate accurate and corpus-based data based on gender-relevant information about the use of idioms in dictionaries, as well as a need to distinguish gender usage restriction from gender usage preference when using gender-marked idioms.